2014
DOI: 10.1371/journal.pone.0091038
|View full text |Cite
|
Sign up to set email alerts
|

Facial Motion Engages Predictive Visual Mechanisms

Abstract: We employed a novel cuing paradigm to assess whether dynamically versus statically presented facial expressions differentially engaged predictive visual mechanisms. Participants were presented with a cueing stimulus that was either the static depiction of a low intensity expressed emotion; or a dynamic sequence evolving from a neutral expression to the low intensity expressed emotion. Following this cue and a backwards mask, participants were presented with a probe face that displayed either the same emotion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…For example, Kilts et al (2003) found that dynamic emotion perception recruited neural correlates implicated in the analysis of emotional information in the animated facial expressions, whereas static emotion perception recruited neural correlates implicated in motor imagery. In addition, compared to static emotional expressions, the animated and changing cues in naturalistic emotional expressions have been found to stimulate greater predictive processing (Kaufman and Johnston, 2014;Palumbo and Jellema, 2013). This is due to the greater uncertainty involved in perceiving dynamic emotions, compared to static emotions, as there is a larger influx of sensory information that is continually evolving and changing over time.…”
Section: Emotion Perceptionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Kilts et al (2003) found that dynamic emotion perception recruited neural correlates implicated in the analysis of emotional information in the animated facial expressions, whereas static emotion perception recruited neural correlates implicated in motor imagery. In addition, compared to static emotional expressions, the animated and changing cues in naturalistic emotional expressions have been found to stimulate greater predictive processing (Kaufman and Johnston, 2014;Palumbo and Jellema, 2013). This is due to the greater uncertainty involved in perceiving dynamic emotions, compared to static emotions, as there is a larger influx of sensory information that is continually evolving and changing over time.…”
Section: Emotion Perceptionmentioning
confidence: 99%
“…Static images only represent a single facial pattern within a single modality and fail to capture the dynamic complexity of emotion perception relevant in everyday life. In addition, it is the dynamics of emotion that preferentially incite predictive mechanisms, leading to a greater reliance on prior expectations (Kaufman and Johnston, 2014;Palumbo and Jellema, 2013). Thus, it is of paramount importance that functional Magnetic Resonance Imaging (fMRI) studies, which investigate the influence of prior expectations on emotion perception, incorporate tasks that rely on multimodal sensory information and dynamic emotional presentations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations